Sub-30 nm 2D Perovskites Patterns via Block Copolymer Guided Self-Assembly for Color Conversion Optical Polarizer - Park, Youjin; Han, Hyowon; Lee, Hyeokjung; Kim, Sohee; Park, Tae Hyun; Jang, Jihye; Kim, Gwanho; Park, Yemin; Lee, Jiyeon; Kim, Dongjun; Kim, Jiwon; Jung, Yeon Sik; et al. (Wiley - V C H Verlag GmbbH & Co., 2023)
Despite the remarkable advances made in the development of 2D perovskites suitable for various high-performance devices, the development of sub-30 nm nanopatterns of 2D perovskites with anisotropic photoelectronic properties remains challenging. Herein, a simple but robust route for fabricating sub-30 nm 1D nanopatterns of 2D perovskites over a large area is presented. This method is based on nanoimprinting a thin precursor film of a 2D perovskite with a topographically pre-patterned hard poly(dimethylsiloxane) mold replicated from a block copolymer nanopattern consisting of guided self-assembled monolayered in-plane cylinders. 1D nanopatterns of various 2D perovskites (A & PRIME;(2)MA(n)(-1)Pb(n)X(3)(n)(+1),A & PRIME; = BA, PEA, X = Br, I) are developed; their enhanced photoluminescence (PL) quantum yields are approximately four times greater than those of the corresponding control flat films. Anisotropic photocurrent is observed because 2D perovskite nanocrystals are embedded in a topological 1D nanopattern. Furthermore, this 1D metal-coated nanopattern of a 2D perovskite is employed as a color conversion optical polarizer, in which polarized PL is developed. This is due to its capability of polarization of an incident light arising from the sub-30 nm line pattern, as well as the PL of the confined 2D perovskite nanocrystals in the pattern.